D7.1 Report on the ECoE research clusters and research groups: management, function and technical capacity - Themistocleous, Kyriacos; Hadjimitsis, Diofantos G.; Michaelides, Silas; Neocleous, Kyriacos; Mamouri, Rodanthi-Elisavet; Tzouvaras, Marios; Mettas, Christodoulos; Schreier, Gunter; Kontoes, Haris; Ansmann, Albert; Komodromos, George (My University, 2022)
This deliverable focuses on the formation of the Eratosthenes Centre of Excellence thematic research clusters of Environment & Climate, the Resilient Society and Big Earth Data Analytics in terms of the operations, research collaborations, tools to facilitate research, agreeing internal structures and allocating staff responsibilities. This deliverable will focus on the integration of recruited research personnel, research equipment and the Strategic Partners’ expertise to meet the needs of the research groups.
Keywords: ERATOSTHENES; Remote Sensing; EXCELSIOR; HORIZON H2020; EMMENA